A multiple indicator model for panel data: an application to ICT area-level variation - Eva Ventura; Albert Satorra (International Telecommunications Society (ITS), 2015)
Consider the case in which we have data from repeated surveys covering several geographic areas, and our goal is to characterize these areas on a latent trait that underlies multiple indicators. This characterization occurs, for example, in surveys of information and communication technologies (ICT) conducted by statistical agencies, the objective of which is to assess the level of ICT in each area and its variation over time. It is often of interest to evaluate the impact of area-specific covariates on the ICT level of the area. This paper develops a methodology based on structural equations models (SEMs) that allows not only the ability to estimate the level of the latent trait in each of the areas (building an ICT index) but also to assess the variation of this index in time, as well as its association with the area-specific covariates. The methodology is illustrated using the ICT annual survey data collected in the Spanish region of Catalonia for the years 2008 to 2011.
Keywords: 330; structural equations model; confirmatory factor analysis; longitudinal analysis; index; digital divide; Information and Communication Technologies (ICT)